Erysense, a Lab-on-a-Chip-Based Point-of-Care Device to Evaluate Red Blood Cell Flow Properties With Multiple Clinical Applications - Recktenwald, Steffen M.; Lopes, Marcelle G. M.; Peter, Stephana; Hof, Sebastian; Simionato, Greta; Peikert, Kevin; Hermann, Andreas; Danek, Adrian; van Bentum, Kai; Eichler, Hermann; Wagner, Christian; Quint, Stephan; et al. (Frontiers in Physiology, 2022)
In many medical disciplines, red blood cells are discovered to be biomarkers since they 'experience' various conditions in basically all organs of the body. Classical examples are diabetes or hypercholesterolemia. However, recently the red blood cell distribution width (RDW), is often referred to, as an unspecific parameter/marker (e.g., for cardiac events or in oncological studies). The measurement of RDW requires venous blood samples to perform the complete blood cell count (CBC). Here, we introduce Erysense, a lab-on-a-chip-based point-of-care device, to evaluate red blood cell flow properties. The capillary chip technology in combination with algorithms based on artificial neural networks allows the detection of very subtle changes in the red blood cell morphology. This flow-based method closely resembles in vivo conditions and blood sample volumes in the sub-microliter range are sufficient. We provide clinical examples for potential applications of Erysense as a diagnostic tool (here: neuroacanthocytosis syndromes (NAS)) and as cellular quality control for red blood cells (here: hemodiafiltration (HDF) and erythrocyte concentrate (EC) storage). Due to the wide range of the applicable flow velocities (0.1 mm/s to 10 mm/s) different mechanical properties of the red blood cells can be addressed with Erysense providing the opportunity for differential diagnosis/judgments. Due to these versatile properties, we anticipate the value of Erysense for further diagnostic, prognostic, and theragnostic applications including but not limited to diabetes, iron deficiency, COVID-19, rheumatism, various red blood cell disorders and anemia, as well as inflammation-based diseases including sepsis.